Essentials of Autopsy Practice Innovations, Updates and Advances in Practice - Rutty, Guy N.; Rutty, Guy N. (Springer London : Imprint: Springer, 2013)
Essentials of Autopsy Practice: Innovations, Updates and Advances in Practice is the fifth volume in the Essentials in Autopsy Practice series, covering topics of current and future interest. Designed to keep all involved in the investigation of death abreast of changes within the field, this volume covers a wide range of topical areas which can be encountered around the world. Essentials of Autopsy Practice: Innovations, Updates and Advances in Practice covers death by drowning; deaths from extreme temperature; the radioactive autopsy; chemical contamination and the autopsy; blast injuries; forensic odontology identification; and determination of the force used to cause an injury. Useful to both trainees and consultants in all specialty areas within pathology, including forensic pathology, Essentials of Autopsy Practice: Innovations, Updates and Advances in Practice also serves as a guide to all those involved in death investigation, i.e. nurses, lawyers, paramedics and police officers.